Screening of Lampung local rice drought tolerance in germination phase - Chrisnawati, Lili; Yulianty, Yulianty; Ernawiati, Eti; Fitriyani, Umilia; Putri, Aprilia Eka (Jurnal Biologi Udayana; Vol 25 No 1 (2021): JURNAL BIOLOGI UDAYANADO - 10.24843/JBIOUNUD.2021.v25.i01.p01, 2021)
Seed germination is one of the most critical stages in plant growth. Screening at this stage can provide preliminary information on drought tolerance. This study aims to evaluate drought tolerance in local Lampung rice varieties Lumbung Sewu Cantik in the germination phase. This study used a completely randomized design with three concentrations of PEG and three replications. The PEG concentrations given were 0%, 10%, and 15%. The observed data were analyzed for variance at the level a test = 0.05 and further analysis used Duncan's Multiple Range Test (DMRT). The results showed that the higher the PEG concentration, the plumulae length and seminal root length of rice decreased. However, in radicles, PEG 20% did not decrease length growth. Giving PEG 20% also did not decrease the dry weight of the radicles and in the seminal roots, there was no significant difference in weight between PEG 10% and PEG 20%. This indicated that Lumbung Sewu Cantik Padi has the potential to tolerate drought in the germination phase.